Application of representative learning design for assessment of common practice tasks in tennis. (March 2019) - Krause, Lyndon; Farrow, Damian; Buszard, Tim; Pinder, Ross; Reid, Machar
Abstract: Objectives: This study assessed the representativeness of four common tennis practice tasks. Design: Cross-sectional. Method: In pairs, ten elite junior male and female tennis players (12.8 ± 1.05 yrs old) performed four, 4-min practice tasks and a 2-set tennis match. The previously validated representative practice assessment tool (RPAT – seeKrause et al., 2018 ) was used to gain subjective assessments of each practice tasks representative design. Additionally, three-dimensional ball and player movement data was collected using an 8-camera HawkEye system. Mixed models were conducted to compare each practice task to matchplay revealing significant differences across a range of shot and movement characteristics. Results: While players hit the ball faster and with more spin they consistently made contact with the ball further behind the baseline and generated fewer winners in most practice tasks compared to matchplay. Conclusion: Common practice tasks are not representative of the shot and movement characteristics typical of matchplay. More careful design of practice appears to be needed. Highlights: Practice promotes cooperative not combative behavior (longer rallies, less winners). Faster ball speeds in practice were negated by hitting from deeper in the court. The RPAT can help coaches improve the representativeness of tennis practice. Selectively changing task constraints alters player shot and movement performance.